FASTABIQ AL-KHAIRᾹT: ISLAMIC CONGREGATION AND EVERYDAY COMPETITION AMONG PURITAN AND TRADITIONALISTS MUSLIM IN ACEH - Syafieh, Syafieh; Noviandy, Noviandy; Amin, Muhammad (Islam Futura, 2022)
This paper explores the contestation between Puritanism and traditionalism in Muslim communities focused oncase studies on the East Coast of Aceh by groups in urban religious recitation. The article addressing to the subject so far concludes that fundamentalism and traditionalism are two theological forces that are constantly in conflict with each other.This paper seeks to demonstrate that while interactions between the two groups are affected by doctrinal disputes, the two culturesare fairly effective in managing diversity, such that disparities in religious beliefs do not result in group tension and mass abuse.The data used in this research were collected through participatory evaluation, in-depth interviews and literature studies.Finally, this paper shows that the Acehnese people's ability to care for tolerance, although it seems clear that the practical tolerance practiced by the people who are the subjects of this research has been redefined and contextualized in line with the situation of a community dominated by traditionalist Muslim groups.